78.3k views
4 votes
NEED HELP PLEASE ANSWER ASAP! (41)

NEED HELP PLEASE ANSWER ASAP! (41)-example-1
User Wbamberg
by
4.5k points

2 Answers

12 votes

Answer:

41. (2) x² - 3x - 4 =0

Explanation:

Question 41

Standard form of polynomial

  • x² - (sum of roots) + product of roots = 0
  • (2) x² - 3x - 4 =0
User Reynman
by
4.9k points
8 votes

Answer:

(2)
x^2-3x-4=0

Explanation:

Standard form of a quadratic equation:
ax^2+bx+c=0

When factoring a quadratic (finding the roots) we find two numbers that multiply to
ac and sum to
b, then rewrite
b as the sum of these two numbers.

So if the roots sum to 3 and multiply to -4, then the two numbers would be 4 and -1.


\implies b=1+-4=-3


\implies ac=1 \cdot -4

As there the leading coefficient is 1,
c=-4.

Therefore, the equation would be:
x^2-3x-4=0

Proof

Factor
x^2-3x-4=0

Find two numbers that multiply to
ac and sum to
b.

The two numbers that multiply to -4 and sum to -3 are: -4 and 1.

Rewrite
b as the sum of these two numbers:


\implies x^2-4x+x-4=0

Factorize the first two terms and the last two terms separately:


\implies x(x-4)+1(x-4)=0

Factor out the common term
(x-4):


\implies (x+1)(x-4)=0

Therefore, the roots are:


(x+1)=0 \implies x=-1


(x-4)=0 \implies x=4

So the sum of the roots is: -1 + 4 = 3

And the product of the roots is: -1 × 4 = -4

Thereby proving that
x^2-3x-4=0 has roots whose sum is 3 and whose product is -4.

User Sean Mickey
by
5.2k points